1990
DOI: 10.1055/s-0038-1645209
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Drug-Dependent Antigen for Quinine-Dependent Antiplatelet Antibodies on GP III a but not that on GPI b, II b or IX on Human Endothelial Cells

Abstract: SummaryIn quinine- and quinidine-induced thrombocytopenic purpura IgG antibodies are known to react in a drug-dependent manner with different combinations of surface glycoproteins (GP) Ib , IIb, IIIa and IX. Because endothelial cells share a number of properties of platelets, including the presence of GP Ilia and GPIb-like proteins, we have compared these two cell types for their quinine-dependent IgG binding abilities. By immunoblotting of endothelial cells, quinine-dependent IgG binding from four patient ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The mechanisms of formation are thought to be by two methods: (i) the formation of new or altered antigenic sites secondary to the binding of quinine (drug dependent) and (ii) the stimulation of true autoantibody formation without the need for drug (drug independent) [18]. It has been shown that endothelial cells share the glycoprotein IIIa quinine-dependent epitope found on platelets [19,20]. Presumably, it is the antibody damage to endothelial cells which leads to the formation of the thrombotic microangiopathy and microangiopathic hemolytic anemia.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms of formation are thought to be by two methods: (i) the formation of new or altered antigenic sites secondary to the binding of quinine (drug dependent) and (ii) the stimulation of true autoantibody formation without the need for drug (drug independent) [18]. It has been shown that endothelial cells share the glycoprotein IIIa quinine-dependent epitope found on platelets [19,20]. Presumably, it is the antibody damage to endothelial cells which leads to the formation of the thrombotic microangiopathy and microangiopathic hemolytic anemia.…”
Section: Discussionmentioning
confidence: 98%
“…DDTP antibodies typically react with monomorphic epitopes on platelet GP, but only in the presence of the drug or a metabolite. Although several platelet GP have been identified as antibody target in DDTP (GPIb/IX (263–265), GPV (266), GPIIb/IIIa (267–271)) antibodies in an individual patient are highly specific for a single GP. Kroll et al (272) investigated sera of 5 patients with carbimazole‐dependent platelet reactive antibodies.…”
Section: Drug‐induced Immune Thrombocytopeniasmentioning
confidence: 99%
“…We have re cently observed that it also carries one of the drug-dependent antigens involved in quinine-induced thrombocytopenia [4]. Be cause the quinine-dependent antigen is ex pressed on GPIIIa on platelets which do not react with anti-PlA1 antibodies, these anti gens are distinct from one another [4], Both these epitopes are present on endothelial cells [5] which express a glycoprotein which is probably identical to GPIIIa [6] on plate lets. The P1A1 epitope lies on a 17-kDa poly peptide obtained after tryptic digestion of GPIIIa [7], This polypeptide is located somewhere within a 66-kDa fragment of GPIIIa which remains associated with platelets after digestion with chymotrypsin [8],…”
Section: Introductionmentioning
confidence: 99%